Hydration of glycolic acid sulfate and lactic acid sulfate: Atmospheric implications. (1st November 2019) - Tsona, Narcisse T.; Du, Lin
Abstract: Organosulfates constitute an important component of secondary organic aerosols. Due to their polar and hydrophilic nature, organosulfates have the ability to bind with water and their water content may substantially affect the hygroscopicity of aerosols. However, there is poor information on how they interact with water and how their hydrates are distributed in the gas-phase. This study uses electronic structure calculations to investigate the structures and thermodynamics of water uptake by glycolic acid sulfate and lactic acid sulfate in the gas-phase, and the equilibrium distributions of their hydrates at varying degrees of humidity and different temperatures. Given the demonstrated diverse role of neutral and charged species in aerosol formation, the hydration of these organosulfates, both electrically neutral and negatively charged (deprotonated) were investigated. We find that electrically neutral glycolic acid sulfate is more extensively hydrated than its deprotonated counterpart, forming relatively high concentrations of mono-, di-, and tri-hydrates at most tropospheric temperatures and relative humidity, while the latter mostly forms the monohydrate at similar conditions. The opposite situation is observed for lactic acid sulfate where the deprotonated form is the most extensively hydrated, despite their hydrates are formed at low concentrations. However, due to high dissociation constants of organosulfates coupled to their increasing partition to the particle phase with increasing relative humidity, the hydrates of electrically neutral organosulfates studied here would mostly partition into the particle phase and reinforce the effects of their corresponding deprotonated counterparts in altering the hygroscopic properties of aerosol particles. This study can serve as a basis to evaluate the hydration pattern of other organosulfates and assess their implications in aerosol formation. Graphical abstract: Image 1 Highlights: The hydration of glycolic acid and lactic acid sulfates was examined. Dry, mono-, and di-hydrates are predicted to coexist at most conditions. They may affect the aerosol hygroscopicity in different ways.